2007
DOI: 10.1111/j.1559-4564.2007.06366.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Chromium and Biotin Improves Coronary Risk Factors in Hypercholesterolemic Type 2 Diabetes Mellitus: A Placebo‐Controlled, Double‐Blind Randomized Clinical Trial

Abstract: Dyslipidemia, often found in type 2 diabetes mellitus (T2DM) patients, plays an important role in the progression of cardiometabolic syndrome. Two essential nutrients, chromium and biotin, may maintain optimal glycemic control. The authors report here a randomized, double-blind placebo-controlled trial (N=348; chromium picolinate and biotin combination [CPB]: 226, placebo: 122; T2DM participants with hemoglobin A1c [HbA1c] >or=7%) evaluating the effects of CPB on lipid and lipoprotein levels. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
(52 reference statements)
1
27
0
2
Order By: Relevance
“…Many in vitro studies and studies in the general population have shown that vitamins and minerals have important roles in improving lipid and lipoprotein metabolism. [6][7][8][9] To our knowledge, this study is the first to evaluate the effects of multivitamin and mineral supplementation on lipid profile in obese subjects. Previous studies have shown that calcium, 6 chromium and biotin, 7 niacin, 8 folate, vitamins B 6 and B 12 9 could improve lipid metabolism, and that vitamin B1, 28 vitamin B6, 29 vitamin C, 30 calcium, 31 magnesium, 32 and zinc 33 also have important roles in improving hypertension.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many in vitro studies and studies in the general population have shown that vitamins and minerals have important roles in improving lipid and lipoprotein metabolism. [6][7][8][9] To our knowledge, this study is the first to evaluate the effects of multivitamin and mineral supplementation on lipid profile in obese subjects. Previous studies have shown that calcium, 6 chromium and biotin, 7 niacin, 8 folate, vitamins B 6 and B 12 9 could improve lipid metabolism, and that vitamin B1, 28 vitamin B6, 29 vitamin C, 30 calcium, 31 magnesium, 32 and zinc 33 also have important roles in improving hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…4 Furthermore, obesity is strongly associated with hyperlipemia, one of the important risk factors of cardiovascular disease. 4,5 Previous studies have shown that vitamins and minerals have an important role in energy and blood lipid metabolism [6][7][8][9] through several mechanisms. [10][11][12][13] Obese individuals are more likely to have either lower blood concentrations or lower bioavailability of minerals and/or vitamins.…”
Section: à2mentioning
confidence: 99%
“…Some studies have found that chromium administration can reduce fasting plasma glucose by 10-38 mg/dL and reduce glycosylated hemoglobin (hemoglobin A 1c ) by approximately 1%. [4][5][6][7][8][9][10][11][12][13] However, other studies have found no significant difference in these values when comparing chromium administration to placebo. [14][15][16][17][18][19][20][21][22][23][24] Variations in response may be attributable to the different forms of chromium studied.…”
mentioning
confidence: 99%
“…Het HbA 1c was aan het begin van de studie 9,5% en daalde gemiddeld met 0,3 tot 0,5% in de verschillende groepen. Er werden tussen de verschillende groepen geen significante verschillen gevonden (1000 microgram versus placebo: 0,0%; 95%-betrouwbaarheidsinterval (BI): -0, 8). Verder werden er ook geen verschillen gevonden in het gewicht, de bloeddruk of de vetspectrumwaarden.…”
Section: Inleidingunclassified